Finding hidden value through mixed-methodology: Lessons From the Discovery Program’s Holistic Approach to Truancy Abatement - Ventura, Holly E. (American journal of criminal justice, 2005)
Policy makers often bemoan the shortcomings and inefficiency of youth development and similar social work programs whose effectiveness cannot be demonstrated by quantifiable performance indicators. This study argues, through illustration of the Odyssey Learning Center’s Discovery Program (an alternative school serving rural Southern youth in an abject poverty context), that program value can only be evidenced through a mixed-methodological evaluation design. Reasons precluding traditional statistical analysis and effectiveness determinations are discussed and alternative conceptualizations of program value are considered.